(untitled) (Al-Qamar, 2021)
It is clear from the blessed character of Hazrat Hasnain﷟ that he was a beacon of sincerity and piety as well as one of the best protectors of his grandfather’s religion. He has never given any harm to the political condition of Islam. Hazrat Hassan﷟ relinquished from His post to unified the political and economical condition of Islam and Hazrat Hussain﷟ agreed on the settlement with Yazeed to avoid disruption in political stability. They both agreed to support their opponents so that the Ummah of Nana ﷺ is united and the enemies of Islam would not even think of attacking Ibraheem﷣ religion. They will sacrifice their lives for the sake of Islam. Finally Hazrat Hussain﷟ sacrificed His own life and turn a new leaf in the history of Islam it will be remembered for ever.